2023
DOI: 10.1525/mp.2023.40.5.353
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Relationship Between Catchiness and Groove

Abstract: Groove and catchiness are central properties of popular music that frequently appear together. Yet, a possible relationship has neither been postulated nor examined. In music psychology, groove is commonly understood as a pleasurable urge to move. Catchiness is often tied to the memorability of music, but it is less researched, and definitions are elusive. In this study, we conducted stimuli-guided expert interviews with popular music creators to unveil their understandings of groove and catchiness based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 51 publications
2
11
1
Order By: Relevance
“…The Pleasure scale includes other affective phenomena—good mood and liking. Hence, it covers a broad part of the positive affect discussed in Bechtold et al [ 59 ]. In previous studies, these two scales were strongly correlated [ 61 , 62 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Pleasure scale includes other affective phenomena—good mood and liking. Hence, it covers a broad part of the positive affect discussed in Bechtold et al [ 59 ]. In previous studies, these two scales were strongly correlated [ 61 , 62 ].…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we explored a possible relationship between groove and catchiness using in-depth expert interviews with music creators, examining how they conceptualize, relate, and employ the two concepts in theory and practice [ 59 ]. The results suggested that musicians think of groove as a bodily experience coupled with positive affect, participation, immersion, and social aspects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…"The groove depends on the precision of timing" is one of the most endorsed statements in Janata et al (2012). Among musicians, the timing topic is crucial to groove (Bechtold et al, 2023) and microtiming is an often-discussed factor for the groove experience (e.g., Câmara & Danielsen, 2020;Keil, 1995;Senn et al, 2016).…”
Section: Text Miningmentioning
confidence: 99%
“…A previous study used free-form interview data to show that the term groove is used in a nuanced and multifaceted way by listeners (Hosken, 2020). An expert interview study showed that musicians working in popular music use groove for describing musical objects and subjective experiences alike, and that they do so with high interindividual consistency (Bechtold et al, 2023). Besides these two interview studies, semantic work on how the term groove is used in spontaneous reactions to music is scarce.…”
mentioning
confidence: 99%